Preparation the Road Student Future Learning Process Takes in Vocational Education - Suharyanto, Agung; Nazarudin, Nazarudin; Thanh Nguyen, Phong; Prasasti Abrar, Andi Ika; Rusli, Ris’an (Opción, 2019)
Considering the world is always changing and lately it often happens disruption, then the world of education is the place for actualization and development potential of the child learners to tread the day before they were full of challenges and uncertainties. With other words, the school is a place to read and predict the future ahead for the children of students, a world which the parents or even teachers are not going to, behold now is who has the need to always learn not only the children of students, but do not lose important is the teachers and the parents, since children this will enter the world that the parents and teachers do not know and are not going to experience it. Train and familiarize teachers students to think critically, creatively, and innovative should be the agenda and commitment to daily which is expected to become a habit and the culture of the school. During this appears impression agenda primary school it only takes place in the room class, and the size of the end of its success is reflected in the report in the form of numbers . The teachers also burdened with the tasks of administrative that are so dense that not had time to read the book and follow the training to enrich the insights of knowledge.They are too scarce to communicate personally with their students.